2013
DOI: 10.1021/jp312033p
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization of Reactive Force Field: Dynamics of the [Nb6O19Hx](8–x)– Lindqvist Polyoxoanion in Bulk Water

Abstract: We present results on parameterization of reactive force field [van Duin, A. C. T.; Dasgupta, S.; Lorant, F.; Goddard, W. A. ReaxFF: A Reactive Force Field for Hydrocarbons. J. Phys. Chem. A 2001, 105, 9396-9409] for investigating the properties of the [Nb6O19Hx]((8-x)-) Lindqvist polyoxoanion, x = 0-8, in water. Force-field parameters were fitted to an extensive data set consisting of structures and energetics obtained at the Perdew-Burke-Ernzerhof density functional level of theory. These parameters can reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Analysis of the standard Mulliken charges reveals the known trend in basicity of the various oxygen sites in the PONb: the calculated atomic charges are −0.943e, −0.994e, and −1.137e for the terminal, central, and bridging oxygen atoms, respectively. As shown in earlier experiments and calculations, the bridging oxygen is the most basic of the exposed atoms of the PONb.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Analysis of the standard Mulliken charges reveals the known trend in basicity of the various oxygen sites in the PONb: the calculated atomic charges are −0.943e, −0.994e, and −1.137e for the terminal, central, and bridging oxygen atoms, respectively. As shown in earlier experiments and calculations, the bridging oxygen is the most basic of the exposed atoms of the PONb.…”
Section: Resultssupporting
confidence: 65%
“…Of the wealth of POM catalysts that have been synthesized over decades, Group-V POMs with Lindqvist ion structure, particularly Nb 6 O 19 8– , are ideal candidates to act as base hydrolysis catalysts due to the high charge density of the exposed oxygen atoms . It is therefore not surprising that alkali salts of the Nb 6 O 19 8– ion have recently been reported to hydrolyze nerve agents. , Computational work on Nb 6 O 19 8– has included structural studies using DFT methods, the proposal (also with DFT methods) of an open-cage intermediate that leads to oxygen exchange with solvent measured with NMR, and a recent molecular dynamics study of the protonation of Nb 6 O 19 8– in aqueous media . However, no mechanistic studies of the base hydrolysis reactions with Nb 6 O 19 8– have been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…43 A similar peak location was reported from the ReaxFF parameters of Lindqvist Polyoxoanion in Bulk Water. 46 The first peak location for the Mg-O pair is observed at 2.0 Å, which represents the Mg-O atomic bond as shown in Fig. 10.…”
Section: Reaxff-md Simulations Of Mgcl 2 Hydratesmentioning
confidence: 94%
“…ReaxFF has a comprehensive parametrization of atomic, bonding, angle, and torsion properties, which can fully address the bond breaking, forming, and polarization effects in complicated chemistry environments . Because of its close accuracy to density functional theory (DFT), and particularly no predesignation of multiple reaction pathways required, ReaxFF MD has been applied for reaction mechanism investigations in a wide variety of materials and fuels, including complex coal and biomass utilization, , which demonstrates its feasibility and potential in investigating complex reaction mechanisms. Table lists coal models and simulation results obtained using ReaxFF MD in recent years.…”
Section: Introductionmentioning
confidence: 99%